2015
DOI: 10.1681/asn.2014090859
|View full text |Cite
|
Sign up to set email alerts
|

A Podocyte-Based Automated Screening Assay Identifies Protective Small Molecules

Abstract: Podocyte injury and loss mark an early step in the pathogenesis of various glomerular diseases, making these cells excellent targets for therapeutics. However, cell-based high-throughput screening assays for the rational development of podocyte-directed therapeutics are currently lacking. Here, we describe a novel high-content screening-based phenotypic assay that analyzes thousands of podocytes per assay condition in 96-well plates to quantitatively measure dose-dependent changes in multiple cellular features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 52 publications
(68 reference statements)
1
56
0
Order By: Relevance
“…Actin cytoskeleton in podocytes is a critical link between various signaling components and the cellular receptors, whereas playing an essential role in providing stable architectural support to the cell. Immunofluorescence microscopy showed that TGF-␤1 induced rearrangement of the actin cytoskeleton resulting in loss of stress fibers in podocytes (58,59), a hallmark of cellular damage, and that this loss of stress fibers was prevented by co-treatment with erlotinib ( Fig. 8A), suggesting a link between TGF-␤1 signaling and ErbB4.…”
Section: Mir-146 In Podocytes and Diabetic Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Actin cytoskeleton in podocytes is a critical link between various signaling components and the cellular receptors, whereas playing an essential role in providing stable architectural support to the cell. Immunofluorescence microscopy showed that TGF-␤1 induced rearrangement of the actin cytoskeleton resulting in loss of stress fibers in podocytes (58,59), a hallmark of cellular damage, and that this loss of stress fibers was prevented by co-treatment with erlotinib ( Fig. 8A), suggesting a link between TGF-␤1 signaling and ErbB4.…”
Section: Mir-146 In Podocytes and Diabetic Injurymentioning
confidence: 99%
“…After incubating with primary antibodies, secondary antibodies and/or Alexa 568-conjugated phalloidin (Life Technologies) were incubated with cells. Stained cells were imaged with a Zeiss 700 LSM confocal microscope (Zeiss, Hartford, CT) and Opera Imaging System (PerkinElmer Life Sciences), as described (58).…”
Section: Mir-146 In Podocytes and Diabetic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our hypothesis, we observed that cilengitide blocked all of the effects of Sdc4 ectodomain that we have observed in podocytes, including the increased surface expression of TRPC6 channels, increased ROS generation, modulation of small GTPases, and activation of NFATc1. In this regard, several antagonists of outside-in integrin signaling have protective effects in animal models of podocyte diseases, including diabetic nephropathy in pigs [49] and rats [50], lipopolysaccharide-induced podocyte effacement [51], acute PAN nephrosis [51], and the early stages of experimental glomerulonephritis [52]. There is also evidence that constitutive activation of α v β3 integrins in podocytes leads to albuminuria, glomerulosclerosis, and activation of Rac1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are important limitations to consider when utilizing such podocyte cell lines, podocyte cell culture has been an instrumental tool for simulating various aspects of glomerular disease biology. From the drug discovery perspective, there remain significant opportunities to take advantage of this cellular system for target evaluation and discovery [13,35].…”
Section: Use Of Podocytes In Phenotypic Screensmentioning
confidence: 99%